Analysis of Train Load Distribution on Concrete Sleepers on the Padang–Lubuk Buaya Rail Line - Nadra Arsyad; Afrilda Sari; Lili Leylani; Utami Dewi Arman; Letri Karmila (Civil Engineering Collaboration, 2026)
The increasing operational speed and axle load of railway transportation require railway track structures capable of distributing loads safely and efficiently. Concrete sleepers play a crucial role in transferring loads from the rails to the ballast while maintaining track stability. This study aims to analyze the distribution of dynamic loads acting on concrete sleepers due to train movement and to evaluate the structural response of the railway track using the Beam on Elastic Foundation (BoEF) approach. The research employed a quantitative analytical method using secondary data obtained from railway technical standards, locomotive specifications, and track geometric parameters in accordance with the Indonesian Ministry of Transportation Regulation No. 60 of 2012. Dynamic loading was determined using the Talbot dynamic factor, followed by calculations of rail deflection, maximum bending moment, shear force, and load distribution to the sleepers based on the Winkler elastic foundation model. The results indicate that train speed significantly influences the magnitude of dynamic loads transmitted through the rail structure. Under the analyzed operating conditions, the calculated dynamic wheel load reached 11.77 kN, while the distributed load acting on the concrete sleeper was approximately 6.44 tons. The analysis demonstrates that the concrete sleeper is capable of distributing loads effectively and maintaining structural stability within the design parameters. These findings provide valuable information for railway track planning, maintenance, and evaluation to improve the safety, durability, and performance of railway infrastructure.